Sod production in Brazil - Bôas, Roberto Lyra Villas [UNESP]; de Godoy, Leandro José Grava [UNESP]; Backes, Clarice; dos Santos, Alessandro José Marques; Carribeiro, Livia Sancinetti (FapUNIFESP (SciELO), 2020)
The history of sod production in Brazil is somewhat recent when compared with conventional agricultural crops. This review describes the beginning of sod production in Brazil and the introduction of Emerald grass, as well as the emergence of Sod Growers Associations, which coincides with the marked expansion of the sector. The grass species and cultivars grown in Brazil are also presented and the main characteristics described. The text also reports few data in sod production area in the country, providing an overview planting evolution and characteristics of the market.
A produção de gramas no Brasil
Keywords: bermudagrass; carpetgrass; turf; turfgrass; zoysiagrass